4‐Aminopyridine attenuates muscle atrophy after sciatic nerve crush injury in mice. Issue 2 (30th May 2019) - Yue, Li; Talukder, M. A.; Gurjar, Anagha; Lee, Jung Il; Noble, Mark; Dirksen, Robert T.; Chakkalakal, Joe; Elfar, John C.
ABSTRACT: Introduction: We recently demonstrated the beneficial effects of 4‐aminopyridine (4‐AP), a potassium channel blocker, in enhancing remyelination and recovery of nerve conduction velocity and motor function after sciatic nerve crush injury in mice. Although muscle atrophy occurs very rapidly after nerve injury, the effect of 4‐AP on muscle atrophy and intrinsic muscle contractile function is largely unknown. Methods: Mice were assigned to sciatic nerve crush injury and no‐injury groups and were followed for 3, 7, and 14 days with/without 4‐AP or saline treatment. Morphological, functional, and transcriptional properties of skeletal muscle were assessed. Results: In addition to improving in vivo function, 4‐AP significantly reduced muscle atrophy with increased muscle fiber diameter and contractile force. Reduced muscle atrophy was associated with attenuated expression of atrophy‐related genes and increased expression of proliferating stem cells. Discussion: These findings provide new insights into the potential therapeutic benefits of 4‐AP against nerve injury‐induced muscle atrophy and dysfunction. Muscle Nerve 60 : 192–201, 2019